Several surfaces with special wettability: Influence on spreading and motion of W/O emulsion droplets. Issue 2 (1st February 2018) - Han, Yunrui; He, Limin; Luo, Xiaoming; Huang, Xin; Shi, Kaiyue
ABSTRACT: Physical and chemical modifications were made on the surface of the aluminum sheet to change the surface properties and superhydrophobic–hydrophilic wettability gradient surface was made on the perspex surface by using microstructure-pattering technique and self-assembled-monolayer method. By using high-speed video camera system and optical tensiometer, this paper discusses the influence of special surfaces with different wettability on spreading and motion of water, oil, and W/O emulsion droplets both experimentally and theoretically. In addition, the paper also discusses the influence of the superhydrophobic–hydrophilic wettability gradient on fluidity of W/O emulsion droplets and the coalescence process of droplets. The results showed that the contact angle of W/O emulsion droplets on the modified surfaces was related to the water and oil distribution at the three-phase line. On the wettability gradient surface, the droplet moved spontaneously when the droplet was located at the junction of the gradient. A quasi-steady theoretical model was used to analyze the driving and resistant forces acting on a droplet to improve the understanding of the self-transport behavior of the droplets. GRAPHICAL ABSTRACT: